Proceso atención de enfermería en paciente adulto de 48 años con apendicectomía y sepsis de herida quirúrgica. - Valdiviezo Córdova, Isabel Canania (2022)
The present clinical case study refers to the Care Process in a 48-year-old adult patient with appendectomy and surgical wound sepsis, Virginia Henderson's conceptual model on needs and human development was applied, which allows assessing the patient, recognizing the signs and symptoms of infection and establish a diagnosis. Becoming a support model to describe the dysfunctionality of functional patterns and nursing care techniques established in the NANDA, NOC, NIC taxonomy in patients with infected post-surgical wounds. The appendectomy in a surgical process that occupies a percentage 83% of the surgical processes in one of the most common procedures techniques performed in the abdominal area the age group without gender dominance the clinical manifestations vary according to the conditions of each one of the affected patients and it is essential to define the diagnosis to apply the necessary diagnostic means to more than the clinic. Surgical complications, especially those that occur due to appendectomy linked to acute appendicitis, although they are not very frequent; The number of patients at risk of morbidity due to complications such as perforations prior to the surgical technique is significant. The surgical wound due to appendectomy is currently one of the causes of morbidity in Ecuador as in other countries. In the year 2017, they registered in Ecuador that it presented a morbidity rate that was the first cause in men with appendectomy 20,693 registered cases.